Lucky Luke. 19, On the Daltons' tail - Goscinny, 1926-1977.; Morris, 1923-; Spear, Luke (Canterbury, Kent [England] : Cinebook, 2009)
When the Dalton Gang escapes from a Texas penitentiary, it is up to Lucky Luke and his horse, Jolly Jumper, to bring the outlaws to justice yet again.
First published: Paris: Dargaud Editeur, c1971, under title: Lucky Luke: Sur la piste des Dalton.
Spine title.
Translated from the French.
4.7
3-6.
3-6
Keywords: Dalton Gang -- Comic books, strips, etc. -- Juvenile fiction; Dalton Gang -- Fiction; Dalton Gang -- Comic books, strips, etc. -- Fiction; Cowboys -- Comic books, strips, etc -- Juvenile fiction; Lucky Luke (Fictitious character) -- Comic books, strips, etc -- Juvenile fiction; Cartoons and comics; Cowboys -- Fiction; Lucky Luke (Fictitious character) -- Fiction; Comic books, strips, etc; Cowhands -- Comic books, strips, etc -- Fiction; Lucky Luke (Fictional character) -- Comic books, strips, etc -- Fiction; Western comic books, strips, etc; West (U.S.) -- Comic books, strips, etc -- Juvenile fiction; West (U.S.) -- Fiction; West (U.S.) -- Comic books, strips, etc -- Fiction; Graphic novels; Western comic books, strips, etc